Editorial: Impacts of Tropical Landscape Change on Human Diet and Local Food Systems - Ickowitz, A.; Powell, B.; Rasmussen, L.V.; Rhemtulla, Jeanine M. (Frontiers Media, 2021)
The impacts of changing diets on land use and land cover has been an important area of research in recent years (Foley et al., 2011; Tilman and Clark, 2014; Fanzo and Davis, 2019; Willett et al., 2019). This special issue looks at the reverse side of this relationship – how land use change affects the diets of local communities living in landscapes where change is taking place. Clear links between forest cover and diet and nutritional outcomes have been shown (Johnson et al., 2013; Ickowitz et al., 2014; Rasolofoson et al., 2018; Fisher et al., 2019), while more recent work has started to disentangle the differential impacts of land use type, composition and configuration on diets and the consumption of specific food groups (Rasmussen et al., 2019; Gergel et al., 2020). This special issue brings together a collection of papers that examine the effects of land use and land use change on diet and nutritional outcomes in the tropics. It assembles papers from a wide range of disciplines, covering the links between forest conservation, deforestation, hydropower development, and changing patterns of agricultural production on diets and nutrition across a range of settings.